Arqueologias de Império - Delfim F. Leão (Classica Digitalia: Humanitas Supplementum - Estudos Monográficos, 2018)
This Portuguese contribution to the debate on the concept of "Empire" brings together 17 essays covering various areas and periods across Antiquity. Biblical sources allow us to structure various categories and organize their related meanings as valuable paths to inform our understating of the idea of "Empire". Egypt first serves as the opportunity to inquire the usefulness of "Empire" as a concept within the larger discussion of periodization in History, as well as the scope and limitations of its definitions, as the observed political dissolution in the Late New Kingdom shows. Regarding Ancient "Mesopotamian Empires", the first "Empire" is usually attributed to the political formulas brought forth by the dynasty of Akkad, which emerged before the hegemony of Babylon. The underlying ideology to Hammurabi's social and military policies through two crucial moments in Babylonian History provides the ground to analyze the emergence of its first hegemony: the war with Elam and the expedition to the Kingdom of Larsa. Approaches to the Anatolian and the Phoenician/Syrian-Palestinian territories follow a methodology focused on myth and religious narratives and the traces of political realities found there, as well as a reflection on the validity of "imperialism" when applied to the Phoenician colonial world. Later Mesopotamian imperial formulas are analyzed within the context of violence, military and ritual: on Jeremias and the rationale for a heavenly justified submission of Judah to the so-called "Neo-Babylonian Empire"; on Nabonidus, the last king of this dynasty; and on the diverging behavior of both Nabonidus and Cyrus to the cult of Marduk. Herodotus, a privileged source for the classical perception of eastern formulas, displays the Persian Empire as the background for different Greek political proposals at play (famously in 3.80-82), and informs us of the queenship and the queens of Ancient Persia. Moreover, the role and status of women in Hellenistic societies is further examined, most notably in its relations to power. The last four essays propose a conceptual genealogy for the idea of imperium through the Roman World: from the representation Ancient Historiography creates of the processes structuring Roman "imperialism" and their agents; the interpretation Suetonius proposes of imperial power and how it ought to be used; to the validity of a certain notion of "globalization" applied to the Late Roman expanse.